2018
DOI: 10.1111/fcsr.12247
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience Among Sojourning Japanese Mothers: Links to Marital Satisfaction and Children's Behavioral Adjustment

Abstract: The purpose of this study was to explore sojourning Japanese mothers’ perceived family resilience. The study used Walsh's Framework of Family Resilience in relation to children's behavioral adjustment, perceived stress, and marital satisfaction. Using a quantitative approach, the findings based on responses from 70 mothers revealed the importance of having a strong “belief system” as an adaptive strategy in response to family relocation. The results also indicated that perceived stress, marital satisfaction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
2
4
0
3
Order By: Relevance
“…In a study focusing on indirect relationship of marital adjustment, perceived stress and family resilience, 107 Japanese immigrant mothers who have children aged 4–8 were interviewed. It was found that perceived stress, marital satisfaction and family were influential on the adaptation of children to their new location (Izumi & Gullón Rivera, 2018 ). In another study investigating marital satisfaction, familial stress and sharing child-care responsibilities, parents stated that coping with the emotions and behaviours of children is the most stressful experience (Ki & Joanne, 2014 ).…”
Section: Marital Adjustment Perceived Stress and Family Resiliencementioning
confidence: 99%
“…In a study focusing on indirect relationship of marital adjustment, perceived stress and family resilience, 107 Japanese immigrant mothers who have children aged 4–8 were interviewed. It was found that perceived stress, marital satisfaction and family were influential on the adaptation of children to their new location (Izumi & Gullón Rivera, 2018 ). In another study investigating marital satisfaction, familial stress and sharing child-care responsibilities, parents stated that coping with the emotions and behaviours of children is the most stressful experience (Ki & Joanne, 2014 ).…”
Section: Marital Adjustment Perceived Stress and Family Resiliencementioning
confidence: 99%
“…(5) family who have children with mental disorders [5,12,13]; (6) family with severely injured children [14]; (7) families of individuals with down syndrome [15]; (8) families who live in cities [16,17]; (9) family that live in other country [18].…”
Section: Discussionmentioning
confidence: 99%
“…Karena satu hal yang diragukan adalah kecenderungan istri mengambil alih tanggung jawab dan keputusan rumah tangga, jika pendapatan istri lebih tinggi dari pada suami (Treas dan Tai, 2012). Berdasarkan penelitian Izumi et al (2018) ditemukan bahwa selain tingkat stress yang dialami oleh ibu rumah tangga, peran kedua orang tua dan keharmonisan pernikahan berpengaruh signifikan terhadap perilaku anakanak.…”
Section: Pendahuluanunclassified
“…Menurut Sumiarti (2008), istri berperan sebagai mitra bagi suami untuk membantu suami menambah penghasilan tanpa harus mengabaikan tugas sebagai seorang istri yang ikut berkiprah membantu keluarga keluar dari masalah keluarga. Selain ikut berperan menambah pendapatan keluarga, hal positif lain yang diperoleh jika ibu rumah tangga bekerja adalah tingkat stress yang dialami menjadi menurun dan meningkatnya keharmonisan pernikahan (Izumi, M. dan Gullon-Rivera, 2018).…”
Section: Pendahuluanunclassified